Modification of Pea Protein by pH-shifting Method and Its Impact on Functional Properties of Starch - XU Zi-hui; XU Zi-han; LI Hao; JI Na; QIN Yang; XIONG Liu; SUN Qing-jie (Liang you shipin ke-ji)
Pea protein has broad market prospects due to its low cost, low fat content, absence of animal cholesterol and low allergenicity. However, its poor solubility limits its application. This paper employs the pH-shifting method to modify pea protein and explores the impact of the optimized modified pea protein on the functional properties of various starches. When the pH-shifted modified pea protein was incorporated into different starch systems, it was observed that the peak viscosity and breakdown value of potato starch decreased, whereas those of corn starch and pea starch, as well as their final viscosity and setback value, increased. Thermal analysis (DSC) revealed that the 7-day retrogradation rates of potato starch, corn starch, and pea starch decreased from 31.61%, 49.94%, and 31.85% to 10.75%, 21.70%, and 18.78%, respectively, indicating that the modified protein effectively inhibits the long-term retrogradation of starches. Resistance starch (RS) assays showed that the RS content of potato, corn, and pea starches increased significantly from 4.2%, 4.8%, and 6.3% to 21.4%, 20.7%, and 17.8%, respectively. These results demonstrate that pH-shifted modified pea protein holds significant potential in improving starch properties and enhancing starch resistance to digestion, particularly promising for broad applications in the food and functional materials industries.